CONTRIBUIÇÃO PARA MELHORIA DA GESTÃO DO SERVIÇO PÚBLICO. Estudo de caso: análise da evolução do desempenho do Inmetro - Ribeiro, Flavio Salema Garcao (2003)
The search for continuous improvement should be intrinsic to all the processes and present in the daily procedures of the organizations that are constantly looking for the implementation of integrated administration through total quality, based on the Approaches of Excellency. In this sense, the present study considers a critical reflection about the effective use of the Evaluation Report of the Federal Government's Quality Award - PQGF, for the National Institute of Metrology, Standardization and Industrial Quality - Inmetro. It treats the period concerning the 1998 award, when the institution has received the silver ribbon award, to conquest lately in 2000 the prize in the gold ribbon category. The dissertation was based in the case study parameters. In this research work the Reports of Administration presented by Inmetro to PQGF and in the Reports of Evaluation guided by the managers of the program to Inmetro, specifically those relative to the cycles of award of 1998 and of 2000, have been used. The theoretical background, was achieved from a bibliographical revision of subjects treated in text Approaches of Excellency of the National Foundation of Quality Award - FPNQ, year 2002, which are the conceptual base of most of the awards implemented in Brazil